The educational venture of the Dutch Reformed Church at Bethesda and Emmarentia Geldenhuys, 1932-1974 : an historical educational study - Seloana, Sepapa Moses (My University, 1997)
Refer to the document
Thesis (M. Ed.) -- University of the North, 1997
Keywords: Education; Dutch Reformed Church; African education; South Africa -- Church history -- 20th Century; Ethical movement (Dutch Reformed Church)